1969
DOI: 10.1104/pp.44.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regulator Induced Movement of Photosynthetic Products Into Fruits of `Black Corinth' Grapes

Abstract: A bstract. The effect of exogenous growth regulators on movement of assimilates into flowers and young fruits of 'Black Corinth' grapes was studied. Clusters were treated with growth regulator and after 0.5 hr to 5 davs the leaves above the clusters were exposed to 14CO. Control shoots received 14CO9 but no growth regulator. At harvest, counting and radioautographic techniques were used to ascertain amount and distribution of activity in clusters. Clusters were dipped in 4-CPA (4-chlorophenoxyacetic acid), GA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

1971
1971
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…It has been shown that GA3 may enhance the export of leaf carbohydrates in grape (20). The greatest increase of W in this study was due to girdling, with smaller increases when girdled vines were sprayed with GA3.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…It has been shown that GA3 may enhance the export of leaf carbohydrates in grape (20). The greatest increase of W in this study was due to girdling, with smaller increases when girdled vines were sprayed with GA3.…”
Section: Resultsmentioning
confidence: 49%
“…GA3 application has been shown to change assimilate distribution in kikuyu grass (7). Cluster or vine GA3 sprays also increased the amount ofassimilates directed into the fruit of Black Corinth grapevines, from the leaf above the cluster (20).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Gibberellins are known to increase the sink capacity in developing flowers of strawberries by increasing cell division and enIargement (Archbold & Dennis 1985) and spraying grape bunches with GA 3 increased the amount of assimilates directed into the fruit from the leaf above the cluster of Black Corinth grapes (Weaver et al 1969). Similareffects have occurred on inflorescences sprayed 2 weeks before full bloom (Motomura 1986).…”
Section: Discussionmentioning
confidence: 85%